Organisational cultures in public and private Portuguese universities: a case study - Ferreira, A.; Hill, M. M. (Higher Education, 2008)
Perceptions of organisational culture made by three categories of staff playing managerial roles in each of two Portuguese Universities (one public and the other private) were compared using a questionnaire adapted from the Organisational Culture Assessment Instrument and translated into Portuguese. The four scales of the questionnaire, designed to measure the Cultures of Clan, Adhocracy, Hierarchy and Market orientation were found to have adequate internal reliabilities, though a factor analysis raised doubts about the construct (factor) validity of two of the scales (Clan and Adhocracy). Application of a MANOVA to scores on the four scales of organisational culture showed, as hypothesised, that the private university was perceived to have significantly stronger cultures of Market orientation and Hierarchy than the public university. No overall difference was found between the universities for the cultures of Clan and Adhocracy. However, general managerial staff in both Universities perceived the cultures of Clan and Adhocracy to be stronger than was the case for technical managerial staff.